2018
DOI: 10.1016/j.diagmicrobio.2017.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Antibody test for Legionella pneumophila detection

Abstract: Legionella pneumophila is responsible for Legionnaires' disease (LD). Its detection in both environmental and clinical samples is mainly performed by culture plate method which requires up to 10days to obtain results. Nowadays, there are commercial antibodies against this bacterium, but they have not been tested against all subgroups of L. pneumophila sg 1 or serogroups 1-16 or their cross-reactions with other non-Legionella bacteria. Indeed, many of these antibodies became available when only 8 serogroups of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…The antibody was selected from a previous work [33] as a specific sensitive antibody for the detection of L. pneumophila. This study confirmed that the LP3IIG2 antibody was able to recognise almost all the serogroups of L. pneumophila and did not cross-react with other microbial species.…”
Section: Legionella Pneumophila Concentration and Antibody Reactionmentioning
confidence: 99%
“…The antibody was selected from a previous work [33] as a specific sensitive antibody for the detection of L. pneumophila. This study confirmed that the LP3IIG2 antibody was able to recognise almost all the serogroups of L. pneumophila and did not cross-react with other microbial species.…”
Section: Legionella Pneumophila Concentration and Antibody Reactionmentioning
confidence: 99%
“…L. pneumophila is the Gram-negative bacterium responsible for Legionnaires' disease, a severe respiratory ailment transmitted through contaminated water droplets [37][38][39]. The global increase in L. pneumophila epidemics emphasizes the need for advanced diagnostic methods [40,41], given the limitations of traditional methods such as culture-based testing and PCR [42][43][44]. Custom-made reactive DC magnetron sputtering equipment was used to prepare the nanoplasmonic thin films composed of Au and Au-Ag NPs dispersed in a TiO 2 dielectric matrix.…”
Section: Introductionmentioning
confidence: 99%